ANALISIS STRATEGI PENGEMBANGAN BISNIS PADA PT GOTO GOJEK TOKOPEDIA UNTUK PERTUMBUHAN JANGKA PANJANG PASCA IPO - Gunawan Aji; Eka Febrianti; Dina Azfia Karima; Ahmad Dhia Iqbal; Nurul Eka Setiani (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
The Indonesian economy is influenced by rapidly expanding startups. Indonesia is one of the five countries with the most startups, demonstrating the country's high level of enthusiasm. PT is one of them. Goto Gojek Tokopedia (GOTO). In the capital cycle, obviously, it can't be isolated from the systems taken by the organization, one of the choices taken by GoTo to get financing or functional capital for the organization is to lead a First sale of stock (Initial public offering) on the Indonesia Stock Trade (IDX). There are two parts to business development strategies: internal environment analysis and external environment analysis. The descriptive qualitative method was used in this study, and the process of collecting data involved conducting literature reviews of scientific publications.